Perbaikan Metode Kerja Menggunakan Maynard Operation Sequence Technique (MOST) dan Metode 5S Untuk Meningkatkan Kapasitas Produksi - Muhammad Dahlan; Arfandi Ahmad; Andi Pawennari; Yan Herdianzah (Universitas Mercu Buana, 2022)
Industrial competition in the era of increasingly fierce globalization forces the industry to struggle to maintain competition. In order to be able to compete in the modern industrial era, not only in terms of the products that will be sold in the market in a short estimated time, but also in terms of all aspects of the industry in it. In this research, the problem that arises is the production process that has not been effective and efficient so that it affects the production time, which is slightly hampered, causing consumer demand not to be fulfilled at CV. Bewrsama's Noble Grace. This study aims to determine the ineffective movements performed by the operator when doing work. Calculating the standard work process time using the Maynard Operation Sequence Technique (MOST) method, to calculate the resulting standard output. Reduction in ineffective processes with 5S work methods. Research was conducted in several divisions starting from the process of receiving milk, processing, milling, and packaging by comparing the effects of MOST between before and after the implementation of 5S. The results obtained are that there are several ineffective movements such as searching, selecting and inspecting which can be reduced by implementing 5S. There was a decrease in the receiving division by 4.7%, processing 0.67%, milling 4.2% and packaging 14.17%. The resulting raw output increased by 4.96% in the packaging division, 2.04% in the processing division, 6.02% in the milling division, and 15.2% in the packaging division.